2019
DOI: 10.1007/s42452-019-1905-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic biomonitoring of airborne particles using lichen transplants over controlled exposure periods

Abstract: Lichens are able to retain airborne pollution-derived particles in their thalli for a long time, and therefore, their use in assessing atmospheric pollution may be suitable and beneficial. In this study, we transplanted species of Parmotrema pilosum in bags and exposed them to atmospheric pollutants at different sites over the course of 1 year. The exposed lichen retained anthropogenic ferrimagnetic Fe oxides that were identified and characterized by environmental magnetism methods, X-ray diffraction analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Bags of Parmotrema pilosum exposed to atmospheric pollutants over the course of 1 year increased from an initial mass-specific magnetic susceptibility value (mean ± S.D.) of 24.1 ± 5.0 × 10 −8 m 3 kg −1 to higher values up to 51.2 ± 23.0 × 10 −8 m 3 kg −1 [48]. This dataset included three sites, two at metallurgical factories, and one influenced by vehicular emissions, where values increased by 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Bags of Parmotrema pilosum exposed to atmospheric pollutants over the course of 1 year increased from an initial mass-specific magnetic susceptibility value (mean ± S.D.) of 24.1 ± 5.0 × 10 −8 m 3 kg −1 to higher values up to 51.2 ± 23.0 × 10 −8 m 3 kg −1 [48]. This dataset included three sites, two at metallurgical factories, and one influenced by vehicular emissions, where values increased by 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Rock magnetism was extensively used also for biomonitoring airborne pollution using tree leaves, barks, mosses and lichens, being efficient PM receptors; for a review, see Hofman et al (2017) , thereinafter, Winkler et al (2019) , Marié at al. (2020) : the magnetic properties of PM filters and bioaccumulators depend on the concentration and the grain-size of magnetite-like minerals accumulated on the samples, with the magnetic susceptibility being the fastest and most used parameter ( Kapper et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such decrease, and hence partial loss of magnetic particles, may be explained by results concluded for transplanted P. pilosum as well. Recently, Marié et al (2020) found decreases of 5-28% in χ after rainy month periods.…”
Section: Comparison Between Campaigns and With Other Related Studiesmentioning
confidence: 98%
“…Magnetic biomonitoring studies have taken advantage of this fact and that magnetic properties of accumulated particles are suitable proxies for pollution, which allow identifying adversely impacted zones within study areas. From the 2010s (Jordanova et al 2010;Salo et al 2012;Chaparro et al 2013;Kodnik et al 2017;Marié et al 2018), three methodologies have been defined for lichens in magnetic biomonitoring, that is, (1) the lichen native species collection; (2) the lichen transplant technique; and (3) "in situ magnetic biomonitoring" or biomonitoring using in situ measurements of magnetic susceptibility, as detailed in Marié et al (2018Marié et al ( , 2020. These methodologies allow us to assess particle pollution; however, differences between them arise from (a) the choice of exposure time for PM collection (weeks, months, years), (b) the possibility of determining the initial conditions of exposure, (c) the preservation species, and (d) the use of available native species to record air pollution over the lichen's life.…”
Section: Introductionmentioning
confidence: 99%